Lingkungan Biofisik dan Emisi Gas CO2 Lahan Gambut Untuk Produksi Biomassa yang Berkelanjutan - Yudi Chadirin; Satyanto Krido Saptomo; . Rudiyanto; Kazutoshi Osawa (Jurnal Ilmu Pertanian Indonesia, 2016)
Environmental biophysics of peatland has high fluctuating by time and its affected on soil CO2 emission. Therefore it is necessary to develop a system for monitoring the biophysical environment and CO2 emissions that can measure continuously to obtain accumulation annual carbon emissions more accurately. The objective of this research was to develop a monitoring system of the environmental biophysics of peatland and CO2 emissions from bare peatlands open. The system of measurement and monitoring of environmental biophysics that have been developed have been able to function properly which includes weather parameters and soil biophysical environment (temperature, soil moisture, and groundwater levels). Carbon emission was measured on an open peat land without vegetation amounting to 62.25 tonnes of CO2/ha/year. Carbon emissions have a positive relationship with soil temperature but has a negative relationship with soil moisture and rainfall.